Effects of diamond content on the morphology and compressive properties of porous aluminum composites - Parveez, Bisma; Jamal, Nur Ayuni; Kusuadi, Nur Izzah Nazurah; Aabid, Abdul; Baig, Muneer (American Chemical Society, 2024)
Porous aluminum (Al) is popular due to its lightweight properties and impact energy absorption. However, it often has a lower mechanical strength than solid Al. To improve the performance, diamond reinforcement was introduced into the matrix. Further, addressing the challenge of interfacial bonding between Al and diamond, coated diamond with varying contents of 5, 10, 15, and 20wt % was added to the porous Al alloy matrix via the powder metallurgy technique. The porosities were formed by using poly-(methyl methacrylate) (30 wt %) as a space holder. The densities of the resultant porous composites ranged from 2.20 to 2.37 g/cm3 and porosities ranged from 33 to 38% for 5−20 wt % diamond contents. Furthermore, the yield strength and plateau stress increased from21.47 to 29.46 MPa and 14 to 20 MPa, respectively, up to 10 wt %diamond content but declined upon further addition. Similarly, the energy absorption capacity increased from 2.15 to 2.95 MJ/m3up to 10 wt % diamond content and thereafter decreased. Thus, the addition of coated diamond and alloying elements in Al strengthened the porous Al composites, making it suitable for applications requiring good compressive strength and energy absorption capacity